Constitutive Model for Fibre Reinforced Cemented Silty Sand. Issue 5 (3rd September 2022) - Safdar, Muhammad; Newson, Tim; Shah, Faheem
ABSTRACT: In this study, a modified version of Severn–Trent constitutive model was used to simulate the mechanical behaviour of composite materials under drained and undrained triaxial compression loading conditions. Two additional parameters obtained from the laboratory tests were added to the standard Severn–Trent model to simulate the stress-strain behaviour of cement and fibre-reinforced Toyoura silty sand. The model parameters were derived based on the experimental results performed, parametric study, trial and error and by comparison with previous research studies. The comparisons covered ranges of material from 0% to 3% fibre, 0% to 3% cement, 20% to 60% relative densities, and silt contents of up to 75%. The experimental results and model simulations were compared in terms of deviatoric stress versus axial strain, volumetric strain versus axial strain, and stress path behaviour. A close agreement of model simulations with the experimental results is observed for many of the tests performed on pure Toyoura sand, cemented, fibre, and fibre-reinforced cemented Toyoura silty sand. The extracted parameters are used to predict the response of those experiments until a reasonable (e.g. ± 5–10% peak strength) comparison is obtained.